UPAYA HUKUM TERHADAP INVESTASI CRYPTOCURRENCY DOGECOIN ILEGAL YANG MERUGIKAN KONSUMEN - Widjangkoro, Hanung (PERSPEKTIF : Kajian Masalah Hukum dan Pembangunan, 2024)
The supply and demand for digital era commodity assets is related to the development of commodity markets. Investing in cryptocurrencies is very attractive as an alternative investment opportunity that has the potential to gain huge profits in a fairly short time. Causing the general public to experience a lack of understanding of the Dogecoin cryptocurrency investment system, which puts investors at risk of experiencing difficulties. government Legal protection for investors and legal certainty when there are regulations are regulated in CoFTRA Regulation Number 5 of 2019 concerning Technical Provisions for the Physical Market of Crypto Assets on the Futures Exchange. This research aims to analyze legal remedies for Dogecoin cryptocurrency investment and legal protection for investors and legal certainty when there are regulations stipulated in Bappebti Regulation Number 5 of 2019 concerning Technical Provisions for the Physical Market of Crypto Assets on the Legal Futures Exchange which is detrimental to consumers. The research approach in this study is a normative legal research method using a statutory and regulatory approach and a contextual approach. Based on the research results, it can be concluded that legal action regarding the Dogecoin Cryptocurrency investment dispute can be resolved through non-litigation and litigation.